PERFORMANCE OF CULTURED White-leg Shrimp IN RICA Probiotic Application METHOD in PONDS AERATED WITH SUPERCHARGE BLOWER - Endang Susianingsih; Koko Kurniawan; Muharijadi Atmomarsono (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
Several ways have been done to encounter shrimp disease affecting cultured shrimp in Indonesian ponds in the last two decades. This research was aimed to find out the effect of different application of probiotic RICA4, RICA5, and RICA3 method on survival rate and production of white-leg shrimp (Litopenaeus vannamei) cultured in ponds aerated with supercharge blower. RICA probiotics are bacteria probiotics produced by the Research and Development Institute for Coastal Aquaculture, originally isolated from seaweed and sea sediment. This experiment was carried out in completely randomized design using nine 250-m2 experimental ponds stocked with 15 shrimp fries/m2. There were three treatments namely: A=alternate use of three probiotics RICA4, RICA5, and RICA3; B=combination use of three probiotics RICA4, RICA5, and RICA3; and C=control (without probiotic), each treatment with three replications and cultured with supercharge blower. Variables observed in this study were survival rate and production of the shrimp calculated at the end of experiment, total vibrio count (TBV) and total plate count of common bacteria (TPC) of the pond waters and sediments monitored every two weeks. The results showed that application of probiotic RICA4, RICA5, and RICA3 applied either in alteration or in combination significantly increased survival rate (P<0.05) but not on production (P>0.05) of the white-leg shrimp. TBV/TPC ratio in the control pond waters after 10-weeks culture (over than 10%) was relatively dangerous for the cultured white-leg shrimp. This shows that application of probiotic could prevent the growth of Vibrio spp in the cultured shrimp pond water.